Integrasi dalam Sistem Pendidikan Islam di Desa Mundu Pesisir Kabupaten Cirebon - Yeti Nurizzati (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2016)
Mundu Pesisir is one of the coastal areas in Cirebon with themajorityof Moslem community that allows rapid development of Islamic education. However, they demanded anintegrated Islamic education in order to produce competent graduates with a good personality. The problems are: How the Islamic education system in this village? What is the percentage of the implementation of an integrated Islamic education there? How is the comparison of the implementation of Islamic education there? This study was an evaluative study with a quantitative comparationalapproach. Selection of samples used proportional stratified random sampling technique with questionnaires distributed to students of DTA Islamiyah 1, MTs Islamiyah and MA Mundu Pesisir. Data was processed using the percentage technique, F test, and Pearson correlation test. Implementation of Islamic education in DTAI 1 Mundu Pesisir, when compared with the characteristics of an integrated Islamic education, reached 91.5%; MTI 86.25%; and MAI 87.25%. Implementation of Islamic education in all three madrasah did not differ significantly at the 5% error level. There was a very strong correlation with a very real significance at 1% error level.Keywords: Islamic Education System, Integration, Mundu Pesisir.